REPURPOSING OF DRUGS: EMERGING SCENARIO - T. Jagadeesh; G. Sathish; M. Parthiban; P. Raja; G. Sarathchandra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In recent times drug repurposing has gained interest over the traditional drug discovery due to reduction in time and cost of development of new drug. Drug repurposing approach has given promising drug candidates for various viral diseases like COVID 19, Ebola, Zika, Dengue, Influenza, HIV, Herpes, etc. Ontarget and off-target are the two basic strategies of drug repurposing. Macrolide, Artemisinin, Quinoline antiparasitic drugs are some of the drugs repurposed against cancer and drugs like thalidomide are repurposed against COVID-19 infection. Repurposing of veterinary drugs like ivermectin, levamisole and benzemidazole group of antiparasitic drugs are also under consideration. This review elaborates repurposing of antihypertensive drugs like angiotensin- converting enzyme inhibitors (ACEI), angiotensin-receptor blockers (ARBs), β-blockers as anti- neoplastic drugs, anti-diabetic drugs against Alzheimer’s disease, fluorophenyl benzimidazole (FPD) as antihypertensive drug, thalidomide against COVID-19 infection, levamisole as antineoplastic drug, benzimidazole as anti-cryptococcal drug and some other new drugs. Usage of in silico techniques and pharmacophore modeling strategies can further accelerate the process of drug repurposing. The drug repurposing strategies significantly minimize research and development costs, provide greater chances of success, shorter research time and lower investment risk.